Управління ринком сільськогосподарської техніки на основі консолідації та прямого маркетингу - Нехай, Вікторія Василівна; Нехай, Виктория Васильевна; Nekhai, Viktoriia (My University, 2015)
UK: У наш час підтримка галузі сільськогосподарського машинобудування, яка є потужною базою функціонування сільського господарства, є актуальним завданням. Саме маркетинг покликаний забезпечити найповніше задоволення потреб аграріїв, спонукає оновлення асортименту сільгосптехніки, у перспективі- розвиває галузь та підтримує беззбиткову діяльність її підприємств. Маркетингове забезпечення товарів, які виробляють підприємства цієї галузі, є необхідністю, викликаною нестабільним збутом. RU: Целью статьи является обоснование гипотезы необходимости и целесообразности применения метода прямого маркетинга организациями консолидированного маркетинга для решения рыночных проблем предприятий сельскохозяйственного машиностроения. Использованы методы анализа, синтеза, семантический, гепотетико- дедуктивный и комплексно целевой подход для исследования маркетинга, как составной части системы управления предприятием. Выдвинута гипотеза и обосновано, что применение прямого маркетинга организациями консолидированного маркетинга позволяет достигать успеха в управлении рынком сельскохозяйственной техники и упрочить показатели ее сбыта. Научная новизна статьи заключается в том, что разработан приемлемый для предприятий исследуемой отрасли перечень составляющих информационного обеспечения процесса исследования рынка и закрепление на нем, а также указано на соответствующие источники информации. На основе собственных исследований выделены вопросы, которые беспокоят покупателей сельхозтехники в процессе принятия решения о покупке. Практическая значимость статьи для руководителей предприятий заключается в разработке действенных маркетинговых мероприятий для налаживания устойчивых отношений с потенциальными покупателями сельхозтехники при условии использования прямого маркетинга. EN: The aim of the article is to study the hypothesis of the need and feasibility of applying the method of direct marketing organizations to consolidate marketing solutions market problems of agricultural engineering enterprises. The methods of analysis, synthesis, semantic, gepotetiko- deductive and comprehensively targeted approach for the study of marketing as an integral part of an enterprise management system. The hypothesis is justified and that the use of direct marketing organizations to consolidate marketing allows you to achieve success in the management of the agricultural machinery market and strengthen its sales figures. Scientific novelty of the article is that developed acceptable for companies investigated industry list of the components of information support of the process of market research and consolidate it, and given to the relevant sources of information. Based on original research highlighted the issues that worry buyers of agricultural machinery in the process of making purchasing decisions. The practical significance of the article for managers is to develop effective marketing activities to establish sustainable relationships with potential buyers of agricultural equipment, provided the use of direct marketing.
Управление рынком сельскохозяйственной техники на основе консолидации и прямого маркетинга
Management of the agricultural machinery market on the basis of the consolidation and direct marketing
Keywords: консолідація; машинободування; ринок; маркетинг; консолидация; машиностроение; прямой маркетинг; рынок; сельскохозяйственная техника; управление; Consolidation; Engineering; Direct Marketing; Market; agricultural technics; management